QUALITY OF LIFE AND BODY COMPOSITION IN PROFESSIONAL NURSES - A CASE STUDY (Fiep Bulletin - online, 2014)
The common sense indicates for the life to be of good quality it is primordial to have health.  As much the physical activity as the physical conditioning it can be necessary for the health and longevity. In the world of the work some tasks depend a lot on the physical capacity of the operator, capacity this in accomplishing tasks that demand energy expense. It was looked for with this work to do a rising diagnosis of the nurses' body composition and as this it can interfere in your quality of life related to the health. The sample was composed by thirty (30) professional nurses. A compass (mark CESCORF®) was used, accurately of 1 mm; a digital scale (mark KRATOS-Cas®), accurately of 5 g; a measuring tape of 1 cm of width and 1 m of length. The data collection was accomplished in reserved room, in the own hospital, in day and time scheduled previously. The relative results to the Body Mass Index (BMI) they showed that most of those tested was in the weight strip recommended for the health and that in agreement with the bibliography already mentioned it presented low risks for the health. Already the referring data to the waist-rip index (WRI) in the male sample they were in your totality classified without risks increased to contract diseases and most of the female sample also without risks. These data revealed that in the sample most of the group presents unfavorable %G in general in agreement with the established parameters for the literature.